Dipeptidyl Peptidase-4 inhibitors use in type II diabetic patients in a tertiary hospital - Woh Yon Mak; Jivanraj R. Nagarajah; Hannah Abdul Halim; Anitha Ramadas; Zulsairi Mohd Pauzi; Lay Ting Pee; Nirmala Jagan (Taylor & Francis Group, 2020)
Background In Malaysia, for more than a decade, dipeptidyl peptidase-4 inhibitors (DPP-4i) are among the oral antidiabetic medications used as monotherapy or in combination to manage type II diabetes mellitus (T2DM). These medications are known for the efficacy in glycated haemoglobin (HbA1c) reduction and weight neutral effect with minimal hypoglycaemia occurrence. This study aimed to identify the outcomes of DPP-4i use in one of the largest tertiary public hospital in Southeast Asia. Methods This is a retrospective cross sectional study conducted in 2016, where stratified sampling method was used. Patients with T2DM treated with available DPP-4i; namely Linagliptin, Saxagliptin, Sitagliptin and Vildagliptin, for at least 3 months were identified from the pharmacy record. Medical records from Physician Clinic in Hospital Kuala Lumpur (HKL) were reviewed. Data on demographic, anthropometric, antidiabetic treatment modalities, laboratory and documented outcomes were collected. Outcomes endpoints which include changes in HbA1c, fasting blood glucose (FBG), and body weight were recorded and analysed. Adverse drug reactions (ADR) documented were also reported. Results and discussion A total of one hundred and five patients were recruited. The patients were 49.5% men (n = 52), with a mean age of 57 years, mean HbA1c of 8.5% (69 mmol/mol) and mean BMI of 29.5 kg/m2. At least 50% of the patients had T2DM for more than 10 years and more than two third of these patients had both T2DM and hypertension. Thirty nine patients were on Vildagliptin, 32 on Sitagliptin, 26 on Saxagliptin and the remaining on Linagliptin. The most commonly prescribed DPP-4i were Vildagliptin and Sitagliptin. Majority of the patients (90.4%) were prescribed with Metformin, with 62.8% of patients on fixed-dose combination, and the remaining on add-on Metformin therapy. Use of DPP-4i as an adjunct was associated with a mean reduction of 0.9% (9 mmol/mol) in HbA1c (p < 0.0001) and 1.15 mmol/L (19.82 mg/dL) in FBG (p = 0.001) without significant weight changes (p = 0.745). Sitagliptin had the highest reduction in HbA1c (1.66%,19 mmol/mol; p-value< 0.0001). Twelve ADRs were reported with the highest report on gastrointestinal intolerance (n = 7). None of the ADR reported caused any significant harm to the patients. Conclusion Overall, use of these DPP-4i as an adjunct antidiabetic was associated with reduction in HbA1c.